Pilot implementation projects in low- and middle-income countries to guide surgical quality improvement using best practice recommendations - Wong, Lye-Yeng; Hussain, Saad; Labib, Michael; Henker, Richard; Efobi, Chizoba; Mokogwu, Ndubuisi; Igunma, Jeremiah Agbons; Minas, Seye Mesfine; Laeke, Tsegazeab; Ferguson, Mark; Yip, Cheng Har; Hill, Andrew; et al. (Frontiers in Health Services, 2025)
BackgroundAdherence to Best Practice Recommendations (BPRs) has been shown to improve morbidity and mortality in surgical healthcare delivery in low and middle-income countries (LMICs).MethodologyThree LMIC healthcare centres in Laos, Nigeria, and Ethiopia were chosen to participate in the implementation pilots through existing cross-collaborative partnerships. Local teams were assembled to conduct needs assessment analyses prior to implementation study design. The projects are ongoing, and preliminary results are presented using descriptive analysis.ResultsThe BPRs chosen for each site were: hand hygiene in Lao PDR, antimicrobial stewardship in Nigeria, and trauma in Ethiopia. The World Health Organization (WHO) hand hygiene observation tool was used to determine baseline hand hygiene compliance in a children's hospital in Lao People Democratic Republic (PDR), revealing that 56.1% of hand hygiene opportunities were missed. A gap analysis was conducted in an academic Nigerian hospital to investigate antibiotic use in surgical patients, which found that 81.2% of antibiotic use was for prophylactic vs. empiric indications. Lastly, the emergency medical technician national curriculum as set by the Ethiopian Ministry of Health was reviewed by local experts and a 15-module supplemental curriculum was developed to include additional topics such as managing large-scale events, transport of emergency patients, advanced life support, and establishing quality standards.ConclusionThrough international collaboration spearheaded by local stakeholders, we initiated baseline needs assessments in 3 countries to identify pillars on which to build-up implementation projects based on BPRs. These scalable pilot projects can be used as a framework to promote further optimization and standardization of safe and quality surgical care in LMICs.